Valoración de escenarios de agresiones sexuales en contextos urbanos: In-EAS, una propuesta de herramienta de análisis espacial = Assessment of sexual assault scenarios in urban contexts: In-EAS, a proposal for a spatial analysis tool - San Juan Guillén, César (Behavior & Law Journal, 2019)
This paper presents a tool for the assessment of sexual aggression scenarios in urban contexts. The In-EAS has been adapted from an inventory originally designed by Vania Ceccato of the KTH Royal Institute of Technology in Sweden. In our context, applied in three medium-sized Spanish cities, we have been able to identify two major types of scenarios of sexual aggression in urban space. A first category of well-maintained spaces, but due to the presence of plant elements with a "panoramic-refuge" effect (i.e. places where one can observe without being seen) offer opportunities to the potential aggressor. The second category includes scenarios that are geographically peripheral and with some indicators of deficiencies in urban maintenance, with the presence of graffiti, abandoned buildings and a very low presence of pedestrians. That is to say, what in the criminological field would serve as an example to illustrate the Broken Windows Theory. On the other hand, they are urban environments in which there is a scarce presence of plant elements, so there is a larger visual field surface that does not result in a greater informal control precisely because of the aforementioned theory of broken windows. The importance of these findings for the prevention of crime through the redesign of spaces is underlined.